Let f(x)= π^2 and g(x) = e^x. Then solve the following equation and

give answer(s) in exact form:
f(x-1)-2∙g(2x-1)=0

1 answer

f(x)= π^2
f(x-1) = π^2, since there is no x in the expression, f(x) = π^2 for all x's

g(x) = e^x
g(2x-1) = e^(2x-1)

f(x-1)-2∙g(2x-1)=0
π^2 - 2 e^(2x-1) = 0
2 e^(2x-1) = π^2
e^(2x-1) = π^2/2
2x - 1 = ln(π^2/2) = 2lnπ - ln2
2x = 2lnπ - ln2 + 1
x = lnπ - (1/2)ln2 + 1/2
Similar Questions
    1. answers icon 1 answer
  1. 1)Solve;2x+1/6=1/2x2)Solve for y in the equation;6y-4/3-2y-1/2=6-5y/6. 3)Solve the equation: 4 sin^2titre+4cos titre=5 for 0°
    1. answers icon 1 answer
    1. answers icon 1 answer
  2. To solve the equation: 24(34+x)=1,20024 ( 34 + x ) = 1 , 200 , give the reasons for each of the given steps. What was done to
    1. answers icon 1 answer
more similar questions